Modelagem de arranjo fotovoltaico com sombreamento parcial para referência de emuladores estáticos - Heringer, Netalianne Mitchelle Fagundes (2016)
The present work consists in modeling a PV array as a reference for PV modules emulators, including partial shadowing effects representation. These emulators are implemented forthe sake of the need to employ maximum power point tracking techniques in solar energy studies and due to the issues to make laboratory tests feasible. PV module rated characteristics are described through a mathematical model, which by computational simulation establishes a reference current to a series connected array emulation. The mathematical model used is adapted to represent the shadowing effects that occur in PV panels, and this reference current is provided to a DC-DC converter. The converter is responsible to represent electrical aspects of array. The partial shadowing adequation algorithm, the emulator design, and the different sun radiation levels and shadowing conditions are considered when presenting the results. By these results it was possible to obtain a suitable representation of series arrays during partial shadowing. The evaluated deviation is kept below manufacturer tolerance levels, for the commercial module used. Designed converter and control worked for all irradiance conditions, with good dynamic behavior. The system is able to properly represent array electric characteristics.